Seroprevalence of measles and natural rubella antibodies among children in Bangui, Central African Republic - Daba Régis; Sosler Stephen; Kipela Jean; Manirakiza Alexandre; Gouandjika-Vasilache Ionela (BMC, 2011)
Abstract Background Passively acquired maternal antibodies are necessary to protect infants against circulating measles virus until they reach the eligible age of vaccination. Likewise, high levels of population immunity must be achieved and maintained to reduce measles virus transmission. This study was undertaken to (1) assess the presence of maternally acquired measles-specific IgG antibodies among infants less than 9 months of age in Bangui, Central African Republic and (2) determine the immune status of vaccination-age children and the concordance with reported vaccination status. A secondary objective was to describe the presence of rubella-specific IgG antibody in the study population. Methods Vaccination history and blood samples were collected from 395 children using blotting paper. Samples were analyzed for the presence of measles-specific IgG antibodies using commercial ELISA kits. Results Measles-specific IgG antibodies were detected in 51.3% of vaccinated children and 27.6% of non-vaccinated children. Maternally derived measles IgG antibodies were present in only 14.8% of infants aged 0-3 months and were absent in all infants aged 4-8 months. The presence of IgG-specific measles antibodies varied among children of vaccination age, from 57.3% for children aged 9 months to 5 years, to 50.6% for children aged 6-9 years and 45.6% for chidren aged 10 years and above. The overall prevalence of rubella-specific IgG was 55.4%, with a high prevalence (87.4%) among children over 10 years of age. Conclusion The findings suggest that despite efforts to accelerate measles control by giving a second dose of measles vaccine, a large number of children remain susceptible to measles virus. Further research is required to determine the geographic extent of immunity gaps and the factors that influence immunity to measles virus in the Central African Republic.